2012
DOI: 10.1186/2046-1682-5-17
|View full text |Cite
|
Sign up to set email alerts
|

Physical constraints on the establishment of intracellular spatial gradients in bacteria

Abstract: BackgroundBacteria dynamically regulate their intricate intracellular organization involving proteins that facilitate cell division, motility, and numerous other processes. Consistent with this sophisticated organization, bacteria are able to create asymmetries and spatial gradients of proteins by localizing signaling pathway components. We use mathematical modeling to investigate the biochemical and physical constraints on the generation of intracellular gradients by the asymmetric localization of a source an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Because the phosphotransfer cascade that activates CtrA is conducted via the intermediate cytosolic protein ChpT, the requirements for maintaining a steady state gradient of CtrA~P are more complex than a canonical gradient established by two factors. In systems with one phosphotransfer step, in which the phosphatase is far from saturating, the gradient decays almost exponentially as a function of the ratio between diffusion of signal and phosphatase rate (Barkai and Shilo, 2009;Tropini et al, 2012;Wartlick et al, 2009), while in systems with a cascade of phosphotransfer steps, co-localization of the pathway components plays a key role in gradient shape (Kholodenko et al, 2010), such as created by scaffolding proteins (Good et al, 2011). Here we demonstrated that a bacterial microdomain exhibits a similar function to eukaryotic scaffolds by sequestering all members of the CtrA activation pathway and effectively combining the forward phosphotransfer activities of CckA and ChpT into one localized enhanced source, generating a gradient of CtrA~P across the entire cell ( Figures 5 and 6).…”
Section: A Sequestered Phospho-signaling Cascade Drives a Gradient Ofmentioning
confidence: 99%
“…Because the phosphotransfer cascade that activates CtrA is conducted via the intermediate cytosolic protein ChpT, the requirements for maintaining a steady state gradient of CtrA~P are more complex than a canonical gradient established by two factors. In systems with one phosphotransfer step, in which the phosphatase is far from saturating, the gradient decays almost exponentially as a function of the ratio between diffusion of signal and phosphatase rate (Barkai and Shilo, 2009;Tropini et al, 2012;Wartlick et al, 2009), while in systems with a cascade of phosphotransfer steps, co-localization of the pathway components plays a key role in gradient shape (Kholodenko et al, 2010), such as created by scaffolding proteins (Good et al, 2011). Here we demonstrated that a bacterial microdomain exhibits a similar function to eukaryotic scaffolds by sequestering all members of the CtrA activation pathway and effectively combining the forward phosphotransfer activities of CckA and ChpT into one localized enhanced source, generating a gradient of CtrA~P across the entire cell ( Figures 5 and 6).…”
Section: A Sequestered Phospho-signaling Cascade Drives a Gradient Ofmentioning
confidence: 99%
“…To gather insights into the effective force applied to the DNA-protein bond, we simulated DNA-biotin-streptavidin and DNA-biotin-NeutrAvidin constructs in a solid-state nanopore subject to electric field of different strength. Such systems have been extensively explored in conventional [40,49,[60][61][62] and nanopore force spectroscopy measurements [63][64][65]. Figure 6A-E illustrate a typical chain of microscopic events following the capture of dsDNA with a NeutrAvidin protein attached to one of its strands via a biotin linker.…”
Section: Effective Force On the Protein-dna Boundmentioning
confidence: 99%
“…A typical example of this heterogeneous distributions is the effect of membranes. Enzymes can interact with the membranes and accumulate, for example in opposite regions of a bacteria [16], see Fig.4(a). A different case corresponds to the accumulation at the membrane of only one type of enzyme, for example the kinases in Fig.4(b), such inhomogeneous distribution induces a gradient between the interior and the exterior of the cytoplasm [13].…”
Section: Spatial Aspects Of Enzymatic Kineticsmentioning
confidence: 99%
“…In particular, kinases and phosphatases may locate in opposite positions inside the cell, e.g. membrane/cytoplasm [12,13], nucleus/cytoplasm [14] or anterior/posterior [15,16]. It may produce the formation of spatial gradients in metabolic reactions.…”
Section: Introductionmentioning
confidence: 99%